THERMAL CONDUCTIVITY TEST VALUE BATAKO HOLLOW WITH RICE HUSK - Rahmaniah Rahmaniah; Akmal Akmal; Muh. Said L (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2015)
Has been conducted research on the measurement of thethermal conductivity in the sample hollow Batako and batako sampleshas been filled rice husk. this research aimed to determine the effect oftemperature changes on two different sample types. In this researchfirst conducted calorific value calculation on two different sampletypes. Then performed the calculation of the conductivity value thenthe conductivity values obtained were compared with the theoreticalvalue of conductivity. Measurement of the temperature value must bechecked every 10 minutes for 6 hours per day within 12 days. Theresults showed that the role of rice husk in the heat absorption systemis very influential. The temperature batako Sample are not filled ricehusk increased faster than rice husk filled bricks so that the value ofthe temperature change will also affect which will affect thecalculation of calorific value. Value of temperature changes on hollowbatako smaller if compared with batako stuffed rice husk. Calculationof calorific value in the hollow batako samples obtained calorificvalues for the lamp 25 W of 18.339 J and batako samples were filledrice husks for lamp 25 W at 17.226 J. While the calorific value of thelamp 40 W for the sample is 28.839 A hollow batako and batakosamples were filled husks calorific value of 33.019 A. The conductivityvalues obtained in the two different types batako samples is 0.339W/moC or in other words equal to the value batako thermalconductivity according to the theory. Test values obtained greatermechanical stress on the batako samplefilled rice husk compared withhollow batako samples.